2004
DOI: 10.1063/1.1810213
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the degradation of polymer light-emitting devices

Abstract: Anode-to-cathode spatially resolved study of polymer light-emitting device degradation has been performed based on a massive planar device structure. The unique device configuration of the extremely large planar frozen-junction light-emitting electrochemical cell allows for the study of device degradation by direct imaging. Constant current stress for an extended period results in a very unusual net luminance increase as opposed to luminance decay. Imaging of the emission zone has shown changes that are consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…[24,26,28,[33][34][35][36][37] For each active material (X = Li, K, Rb), we recorded 4-5 independent sets, each containing approximately 300 photographs, of the entire p-n junction formation process. [38] By analyzing each set of photographs with a custom program in Matlab (The MathWorks), we were able to calculate the position of the p-type doping front as a function of time during device turn-on.…”
Section: Resultsmentioning
confidence: 99%
“…[24,26,28,[33][34][35][36][37] For each active material (X = Li, K, Rb), we recorded 4-5 independent sets, each containing approximately 300 photographs, of the entire p-n junction formation process. [38] By analyzing each set of photographs with a custom program in Matlab (The MathWorks), we were able to calculate the position of the p-type doping front as a function of time during device turn-on.…”
Section: Resultsmentioning
confidence: 99%
“…LECs operating within the frozen-junction regime have also demonstrated fast turn-on times and relatively long light-emission lifetimes, [23,[27][28][29][30] but some anomalous experimental results, notably a low rectification ratio in conjunction with unipolar light emission and/or a significantly lower stability of the current compared to the light emission, have also been reported. [27,30,31] In this article, we employ a planar surface cell geometry (for a schematic of the structure see the bottom part of Fig. 1) to show that, for certain combinations of active material and electrode, the part of the proposed operational mechanism that assumes the formation of a continuous light-emitting p-i-n junction needs to be revised.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Shin et al further developed this concept when they demonstrated that it is possible to turn on wide-gap devices at low voltages. 28 In this article, we employ this type of planar device to demonstrate that doping front propagation ͑or turn-on time͒ in LECs is limited by ion motion in the undoped region, and consequently that a significant electric field is located in this undoped region between the two doping fronts during the turn-on process.…”
Section: Introductionmentioning
confidence: 99%